Tessellate S.T.E.M.S (2019) - Physics - Category C - Set 2 - Objective Problem 1

Consider a dynamical system governed by the Lagrangian L = m x ˙ y ˙ b ( x y ˙ x ˙ y ) k x y L = m\dot{x}\dot{y} - b(x\dot{y}-\dot{x}y)-kxy . Find the Euler Lagrange equation of dynamical system.

m x ¨ + 2 b x ˙ + k x = 0 m\ddot{x} + 2b\dot{x} +kx = 0 and m y ¨ 2 b y ˙ + k y = 0 m\ddot{y} - 2b\dot{y} +ky = 0 m x ¨ + k x = 0 m\ddot{x}+kx = 0 and m y ¨ + k y = 0 m\ddot{y}+ky=0 m x ¨ + k x = 0 m\ddot{x}+kx = 0 and m y ¨ k y = 0 m\ddot{y}-ky=0 m x ¨ 2 b x ˙ + k x = 0 m\ddot{x} - 2b\dot{x} +kx = 0 and m y ¨ + 2 b y ˙ + k y = 0 m\ddot{y} + 2b\dot{y} +ky = 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Steven Chase
Jan 6, 2019

Here are the Euler Lagrange equations:

d d t L x ˙ = L x d d t L y ˙ = L y \large{\frac{d}{dt} \frac{\partial{L}}{\partial{\dot{x}}} = \frac{\partial{L}}{\partial{x}} \\ \frac{d}{dt} \frac{\partial{L}}{\partial{\dot{y}}} = \frac{\partial{L}}{\partial{y}}}

Evaluating the x x EL equation step by step:

L x ˙ = m y ˙ + b y d d t L x ˙ = m y ¨ + b y ˙ L x = b y ˙ k y m y ¨ + 2 b y ˙ + k y = 0 \large{\frac{\partial{L}}{\partial{\dot{x}}} = m \dot{y} + b y \\ \frac{d}{dt} \frac{\partial{L}}{\partial{\dot{x}}} = m \ddot{y} + b \dot{y} \\ \frac{\partial{L}}{\partial{x}} = -b \dot{y} - ky \\ \boxed{m \ddot{y} + 2 b \dot{y} + k y = 0}}

Evaluating the y y EL equation step by step:

L y ˙ = m x ˙ b x d d t L y ˙ = m x ¨ b x ˙ L y = b x ˙ k x m x ¨ 2 b x ˙ + k x = 0 \large{\frac{\partial{L}}{\partial{\dot{y}}} = m \dot{x} - b x \\ \frac{d}{dt} \frac{\partial{L}}{\partial{\dot{y}}} = m \ddot{x} - b \dot{x} \\ \frac{\partial{L}}{\partial{y}} = b \dot{x} - kx \\ \boxed{m \ddot{x} - 2 b \dot{x} + k x = 0}}

Nice. Two equations of motion for two generalised coordinates. That's how I did it.

Krishna Karthik - 2 years, 2 months ago
Tristan Goodman
Jan 4, 2019

Differentiate the langrangian with respect to the time derivative of X, then differentiate the resulting expression with respect to time. Subtract from this result, the derivative of the langrangian with respect to X. Repeat this process for Y and it's derivative and the answer follows.

Hi Tristan, You are correct, the problem has been edited. Thanks for catching the mistake!

Tessellate S.T.E.M.S Physics - 2 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...